Navigating the Linguistic Labyrinth: Challenges of Using Phrasal Verbs for L2 Learners: Menjelajah Labirin Linguistik: Tantangan Penggunaan Frasa Kata Kerja untuk Pembelajar L2 - Dajang, Innocent Nasuk; Gongse, John Daber (Himpunan Sarjana Kesusastraan Indonesia (HISKI) Komisariat Kalimantan Timur, 2024)
The acquisition and usage of phrasal verbs present significant challenges for second language (L2) learners due to their complex and idiomatic nature. This paper explores these difficulties through a multifaceted analysis of the linguistic and cognitive obstacles that phrasal verbs pose to learners. The study examines the study's participants, which can lead to misunderstandings and misinterpretations. The paper delves into the learners’ competence levels and other issues affecting their ability to grasp phrasal verbs, which often affects their competence and performance in this area of English grammar. The paper also discusses the pedagogical approaches that have helped to facilitate the learners’ learning of phrasal verbs, such as contextual learning, teachers’ ability, corpora, and technology-based tools. The research findings underscore the importance of innovative teaching strategies and continuous practice for L2 learners to effectively navigate the linguistic labyrinth of phrasal verbs. By identifying key challenges and potential solutions, this paper contributes valuable insights into the complexities of language acquisition and offers practical recommendations for educators and learners alike. Ultimately, it aims to enhance our understanding of the intricate relationship between language, culture, and cognition in the context of L2 learning.